Effect of boron carbide nano particles in CuSi4Zn14 silicone bronze nanocomposites on matrix powder surface morphology and structural evolution via mechanical alloying. Issue 3 (15th February 2019) - Clinktan, R.; Senthil, V.; Ramkumar, K.R.; Sivasankaran, S.; Al-Mufadi, Fahad A.
Abstract: In the present research work, [82Cu4Si14Zn]100-x – x wt% B4 C (x = 0, 3, 6, 9, and 12) nanocomposite powders had synthesized by mechanical alloying (MA). The MA process had carried out in a single vial high-energy planetary ball mill with the ball-to-powder ratio of 10:1 for 20 h. The results had revealed that the addition of B4 C nano-ceramic particles had contributed more reduction on Cu-Zn-Si matrix powder particle size, changes in shapes, and structural refinement. The synthesized nanocomposite powders had characterized by advanced microscopes. The calculated average nanocomposite powder particle size was 13 ± 1.2 µm, 9 ± 0.8 µm, 5 ± 0.65 µm, 3 ± 0.4 µm, and 1 ± 0.25 µm for 0, 3, 6, 9, and 12 wt% B4 C reinforced nanocomposite powders respectively. Further, an average nanocrystallite size of 84 nm had obtained for [CuSi4Zn14]-0% B4 C sample whereas 13 nm had achieved for [CuSi4Zn14]-12% B4 C sample. This had attributed by variation in repeated cold welding, severe plastic deformation, and fragmentation of mechanical collisions with the function of boron carbide (B4 C) nano-ceramic particles in Cu-Zn-Si matrix. In addition, the laser powder particle size (diameter, μm) and its distribution at D100, D10, D5, D1, D0.1, and D0.01 with the function of the percentage of B4 C ceramic particles had also studied and investigated.